2010
DOI: 10.1097/gme.0b013e3181c1ac01
|View full text |Cite
|
Sign up to set email alerts
|

Ospemifene effectively treats vulvovaginal atrophy in postmenopausal women

Abstract: Ospemifene was shown to be effective and well tolerated for the treatment of the symptoms of vaginal dryness and dyspareunia associated with vulvovaginal atrophy over and above the use of provided lubricants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
223
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(243 citation statements)
references
References 17 publications
17
223
0
3
Order By: Relevance
“…15 The initial 12-week study evaluated the efficacy and tolerability of ospemifene 30 mg/d and 60 mg/d in 826 women (ospemifene 30 mg, n ¼ 282; ospemifene 60 mg, n ¼ 276; placebo, n ¼ 268). 13 After completing the initial study, women with a uterus were eligible to continue blinded treatment for a total of 52 weeks (12 weeks in the initial study plus 40 weeks in the safety extension [N ¼ 180]). Safety assessments of the breast included mammograms and palpation on physical examination performed at week 52 or study discontinuation.…”
Section: Clinical Studies Of Ospemifenementioning
confidence: 99%
See 2 more Smart Citations
“…15 The initial 12-week study evaluated the efficacy and tolerability of ospemifene 30 mg/d and 60 mg/d in 826 women (ospemifene 30 mg, n ¼ 282; ospemifene 60 mg, n ¼ 276; placebo, n ¼ 268). 13 After completing the initial study, women with a uterus were eligible to continue blinded treatment for a total of 52 weeks (12 weeks in the initial study plus 40 weeks in the safety extension [N ¼ 180]). Safety assessments of the breast included mammograms and palpation on physical examination performed at week 52 or study discontinuation.…”
Section: Clinical Studies Of Ospemifenementioning
confidence: 99%
“…26,29 In three phase 3 clinical trials, ospemifene has been demonstrated to be effective and generally well tolerated in the treatment of dyspareunia, a symptom of moderate to severe VVA in postmenopausal women. 13,[30][31][32] In addition, many preclinical evaluations of ospemifene have been conducted to determine its activity in breast cancer tissue ( Table 2). [8][9][10]14,33 Although breast cancer models differ from healthy breast tissue, the preclinical studies are a starting point for further research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained data suggests, that the improvement confirmed by FSFI is not related to serum hormone changes but demonstrate the beneficial effect of ospemifene on vaginal mucosa. Other authors also described the effectiveness of ospemifene compared to a placebo as well as the safety of this therapy [38][39][40][41][42]. A recent review on ospemifene in the VVA treatment reported also that an oestrogenic effect of ospemifene on the bone is comparable to the bone-restoring activity of raloxifene.…”
Section: Selective Oestrogen Receptors Modulatorsmentioning
confidence: 93%
“…Ospemifene is a selective estrogen receptor modulator (SERM) [31]. Several studies have shown efficacy [32][33][34][35][36][37][38]. A pivotal 12 week randomized trial showed that ospemifene was shown to be effective and well tolerated for the treatment of the symptoms of vaginal dryness and dyspareunia associated with vulvovaginal atrophy over and above the use of provided lubricants [32].Subsequent studies have confirmed efficacy and safety over 12 months.…”
Section: Ospemifenementioning
confidence: 95%